Publisher Correction: Sex-dimorphic genetic effects and novel loci for fasting glucose and insulin variability - Vasiliki Lagou (Nature Portfolio, 2021)
A Correction to this paper has been published: https://doi.org/10.1038/s41467-021-21276-3